Alternative vertebrate and invertebrate model organisms show similar sensitivity as rodents to a diverse set of chemicals - Hayot, Gaëlle; Lloyd, Gavin R.; Diwan, Gaurav; Keith, Nathan; Smoot, Shannon R.; Cramer von Clausbruch, Christina A.; Kaufman, Thomas C.; Barnard, Marianne; Tindall, Andrew J.; Glaholt, Stephen P.; Massei, Riccardo; Martínez, Rubén; et al. (Environmental science & technology, 2025)
Current regulations aimed at safeguarding human health and the environment from chemical risks require toxicity testing, while regulatory bodies worldwide are phasing out the use of protected animals. Here, we systematically produced toxicity data from five alternative nonmammalian model organisms and a human cell line to demonstrate similarities and differences among distantly related species in their responses to chemical exposure (concentration range 1.8 pM to 2.1 M). We show that Daphnia magna and Danio rerio embryos are affected by more chemicals than Xenopus laevis embryos, Drosophila melanogaster and Caenorhabditis elegans. Lethality/immotility data assembled 72 diverse chemicals into 11 clusters, revealing species-specific outcomes and showing differential enrichment of the clusters for certain chemical structures and modes of action. The ranked relative toxicities of chemicals across the model organisms were highly correlated (Spearman’s correlation, maximum rho = 0.86, p-value = 0; minimum rho = 0.57, p-value = 0.000312), and their average toxicity values closely matched published values for rodents (rat: rho = 0.88, p = 2.8e-06; mouse: rho = 0.88, p = 2.7e-06). Our findings suggest that chemical toxicity under standardized experimental conditions is broadly conserved across a phylogenetically diverse set of model organisms, providing a conservative estimate of mammalian toxicity.
Online veröffentlicht: 24. November 2025
Gesehen am 29.01.2026